Wireless Blood Pressure Monitor with Android Integration: Tracking Systolic and Diastolic Parameters - Sintiyah, Elisa Ayu; Sumber, Sumber; Yudha Setiawan, Singgih (Jurnal Teknokes, 2024)
Blood pressure measurement plays a crucial role in detecting underlying diseases in the human body. It enables the identification of conditions like heart failure, kidney failure, liver damage, and stroke, underscoring the importance of regular measurements. To facilitate independent and routine blood pressure monitoring, the development of an automatic blood pressure measuring device is essential. This research aims to design and fabricate a digital sphygmomanometer that can transmit measurements to a smartphone through the Blynk application. The blood pressure measurement is conducted using the MPX5050GP pressure sensor as the pressure detector. The device is programmed using the Esp32 microcontroller and incorporates an LCD screen to display the measurement results. The study involved measuring six participants, with each individual's blood pressure recorded ten times. The obtained measurements were then compared to those of the Omron HEM-7120 digital sphygmomanometer. The results revealed a discrepancy of ±9 mmHg in systolic values and ±7 mmHg in diastolic values between the two devices. The smallest systolic error observed was 0.4%, while the largest error reached 3%. Similarly, the smallest diastolic error was 2%, with the largest error recorded at 4.8%. The measurement errors, particularly in diastolic pressure, were influenced by the participants' fatigue, as the repeated measurements on the same arm led to slight arm movements during the process. The study demonstrated the successful transmission of measurement results to a smartphone, affirming the efficacy of the Blynk application. Additionally, the MPX5050GP sensor proved effective indetecting blood pressure. These findings highlight the potential of the developed digital sphygmomanometer as a reliable tool for blood pressure monitoring, promoting self-care and early detection of health issues.